Seguridade social: Por uma análise macrossetorial - Luciana Jaccoud (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The objective of this text is to rescue the perspective of social welfare macro sectorial analysis. The emergence of social security and the interrelation among social security, social assistance and health policies are analyzed, at first, from a historical and conceptual perspective and mobilizing the analytical categories that inform this debate. Then, from a review of studies and research on the relationship among between inequality and mortality, morbidity, disability and dependence, it was possible to identify interfaces between different types of inequalities, as well as mutual relationships between the social welfare policies that seek to face them. After identifying both empirical and conceptual difficulties in carrying out macro-sectoral analyses, it is proposed to mobilize the concepts of institutional complementarity and interdependence in order to favor a better assessment of the reciprocal sectoral influences both in institutional processes and in their results.
Keywords: I31; 330; social welfare; health; social assistance; social security; inequality; coordination; interdependence; institutional complementarity